17. KERJASAMA PEMERINTAH FILIPINA DENGAN INDONESIA DAN MALAYSIA DALAM MENANGANI KASUS SEX TRAFFICKING DI FILIPINA PADA TAHUN 2006-2014 - Dwi Iswahyudi; Tri Cahyo Utomo; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2016)
The Philippines has become a source, transit, and destination of all forms of humantrafficking, especially for sexual exploitation or known as sex trafficking. In handling thecases, Philippines is cooperated with Indonesia and Malaysia where both of them have adirect border with the Philippines. This study aimed to analyze the shape and result ofcooperation between Philippines, Indonesia, and Malaysia in handling sex trafficking casesin the year 2006-2014. In analyzing the cooperation, this study using the theory ofneoliberal institutionalism and also using qualitative method with descriptive typeanalyticaltechniques is through interviews, and literature. In this study it can be seen thatthe cooperation conducted by Philippines with Indonesia and Malaysia have a considerableimpact in the process of handling of trafficking problem in the Philippines. Thecooperation among the three countries had increased vigilance of security in the borderregion and the country gave rise to the role of civil society and non-governmentalorganizations in helping to maximize the business. Through the Trafficking In PersonsReport, the Philippines became the only country in Southeast Asia that has the highestranked in meeting the minimum standards for the elimination of trafficking.